What's new and what's next for biological and targeted synthetic treatments in psoriatic arthritis?. (2nd December 2022) - Sunzini, Flavia; D'Antonio, Arianna; Fatica, Mauro; Triggianese, Paola; Conigliaro, Paola; Greco, Elisabetta; Bergamini, Alberto; Chimenti, Maria Sole
ABSTRACT: Introduction: Psoriatic arthritis (PsA) is a chronic arthritis typically associated with cutaneous psoriasis (PsO). Its pathogenesis is connected to an innate and acquired immune response, as well as genetic risk alleles. The extent of immunopathogenic mechanisms and the heterogenicity of clinical manifestation make the identification of patient-targeted therapies a critical issue, and the treatment decision challenging in patients' management. Areas covered: This review includes a brief overview of biological and small-molecule therapies, focusing on evidence from clinical trials and real-world data that support their use in PsA. We summarize novel and future possible therapeutic strategies, the importance that comorbidities have on selection of therapy and discuss the adverse event of each drug. Relevant papers for up to 1 August 2022 (trials, real-life studies, and reviews) regarding biologics and/or small molecules were summarized. Expert opinion: In recent years, the treatment of PsA has been revolutionized by new targeted therapies, which offer the opportunity to perform a tailored-tail management, considering risk factors, comorbidities, and the different PsA phenotypes. Growing experience with these new agents allows novel treatment approaches that may improve clinical outcomes for PsA patients, in terms of remission/low disease activity and quality of life.